A Study Of The Knowledge Of Blood Transfusion Process Amongst Patients Receiving Blood - Hyder, Shameem; Islam, M Ashadul; Sultan, Murad; Rahman, Mohammad M; Rahman, Syeda M; Rahman, Mujibur (Journal of Chittagong Medical College Teachers’ Association, 2013)
An observational study conducted by reviewing the knowledge of blood transfusion process amongst blood recipients. Total 126 patients who required blood transfusion were entered in this crosssectional study conducted at The National Institute of Trauma & Orthopedic Rehabilitation (NITOR) having full technical support from the Department of Transfusion Medicine, Bangabandhu Sheikh Mujib Medical University (BSMMU) between the period 01 April 2008 and 31 August 2009. The study results showed that 74.1% male and 73.3% female blood recipients are aware of different stages of blood transfusion process that carried out during the treatment. In literate group, 91.4% showed some sort of knowledge on blood grouping, cross-matching, transfusion reactions and donor blood screening tests for HIV/AIDS and other transfusion transmissible infections, whereas, in illiterate group it was observed in 8.6%. Significance of difference was observed in two groups (p=0.001). In both groups misconception about risks and benefits of blood transfusion, panic and lack of knowledge about safety issues of transfusion were observed. Illiterate group have poor understanding on blood transfusion process as expected. The level of education of literate group in this study population is minimum primary education. The findings indicate that in clinical setting there is need to educate the patients on the basic knowledge about the process of blood collection, importance of blood screening, safe use of blood, blood grouping, cross matching and the immediate and delayed complications of blood transfusion including the benefits associated with blood transfusion. This education is equally necessary for general people. JCMCTA 2013; 24 (1):46-49